Clonidine Toxicity: One or More Tablets can be Dangerous in Toddlers - Kini, Sandesh; Bhat Y, Ramesh; Kousika, Phalguna; Thunga, Chennakeshava (Journal of Nepal Paediatric Society, 2019)
Clonidine was a popular anti-hypertensive drug during the 1970s but is less commonly used now. In children clonidine is used to treat attention deficit hyperactive disorder (ADHD). We report a toddler who accidentally ingested 0.3 mg of clonidine and developed respiratory failure with hypotension requiring ventilatory support and inotropes but recovered completely within one week. In any case scenario, when a previously healthy child presents with sudden onset respiratory failure, we should keep a high index of suspicion of clonidine use by anyone at home and its easy accessibility to the child.